2004
DOI: 10.1590/s0034-89102004000500009
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of WHO-17D and Brazilian 17DD yellow fever vaccines: a randomized trial

Abstract: ObjectiveTo compare the immunogenicity of three yellow fever vaccines from WHO-17D and Brazilian 17DD substrains (different seed-lots). Methods An equivalence trial was carried out involving 1,087 adults in Rio de Janeiro. Vaccines produced by Bio-Manguinhos, Fiocruz (Rio de Janeiro, Brazil) were administered following standardized procedures adapted to allow blocked randomized allocation of participants to coded vaccine types (double-blind). Neutralizing yellow fever antibody titters were compared in pre-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 13 publications
(13 reference statements)
2
33
0
4
Order By: Relevance
“…10,11,23 Protective immunity after YF vaccination. Twelve studies in 11 articles 6,10,[25][26][27][28][29][30][31][32][33] addressed the efficacy of YF vaccine in terms of immunogenicity (Table 3). Seroconversion rates were consistently 90% in 9 of 10 studies.…”
Section: Resultsmentioning
confidence: 99%
“…10,11,23 Protective immunity after YF vaccination. Twelve studies in 11 articles 6,10,[25][26][27][28][29][30][31][32][33] addressed the efficacy of YF vaccine in terms of immunogenicity (Table 3). Seroconversion rates were consistently 90% in 9 of 10 studies.…”
Section: Resultsmentioning
confidence: 99%
“…3 The frequency of signs and symptoms on the injection site reported in the literature varied from nil to 39%. 5,7,[9][10][11]14,15,17,18,20,22,23 In all studies, pain on the site of injection was the most frequently reported local adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…3 A physician was available for intervention on acute health problems during immunization procedures. Participants with liver enzymes levels twice or more the upper normal limit were referred for further investigation.…”
Section: Methodsmentioning
confidence: 99%
“…Concordantly, the generation of neutralizing antibodies is a hallmark of protective antiviral immunity against the YF17D virus. 27,28 Neutralizing antibodies directed against structural protein E is believed to be the most critical in terms of protection. 29,30 These neutralizing antibodies may persist for 40 y post vaccination, which exhibits the ability of the virus to elicit an efficient immune response that will result in a long-lived humoral response.…”
Section: Immunological Aspects Of Vaccination With the Yellow Fever 1mentioning
confidence: 99%